Gender Gaps Under Integrated Watershed Management Project in Uttarakhand - Singh, Shikha; Bhardwaj, Neelam (Indian Journal of Extension Education, 2020)
Women share major responsibility in conservation of natural resources through their participation in watershed management activities, but quantifying their role and participation in Integrated Watershed Management Project activities remains a challenge at all levels. Therefore, the present study was carried out to reveal the gaps in gender sensitive policies under Integrated Watershed Management Project in purposively selected Uttarkashi and Bageshwar districts of Uttarakhand. Majority of the watershed management activities were performed by women except construction of stone barrier, mulching and tree planting. The total time spent by men was 6.58 hours per day whereas women spent 10 hours per day on watershed management activities. In the activities like terracing, broad beds, slopping land and nursery raising, majority of the decisions were jointly taken. There was total control of men over land, credit, agricultural produce, inputs, agricultural tools, marketing of farm produce and livestock. On the other hand, women had very little control over marketing of farm produce and livestock. The findings revealed highest gender gap (74.08%) in the field of ownership and minimum gap (18.92%) with respect to participation in watershed management activities.